Vitae medicorum Gedanensium – rękopis z połowy XVIII w. ze zbiorów Biblioteki Gdańskiej Polskiej Akademii Nauk - Siek, Bartłomiej; Szarszewski, Adam (Studia Źródłoznawcze. Commentationes, 2015)
Vitae medicorumGedanensium – a Manuscript from the Mid–eighteenth Century in the Collections of the Gdańsk Library of the Polish Academy of Sciences One of the most interesting archival sources for the history of medicine in Gdańsk is a manuscript in the Gdańsk Library of the Polish Academy of Sciences (Ms514), containing biographies of local physicians. Vitae medicorum Gedanensium, qui tum apudsuos tum apudexteros floruerunt originates from the library of V. Schlieff (1680–1750) and is attributed to the Gdańsk physician L. von Hammen (1651–1689). An analysis of the source, however, leads to the conclusion that this is a copy of the von Hammen manuscript in an unknown handwriting. The handwriting of the numerous later supplements is that of von Hammen, with Schlieff expanding the information in the biogrammes. The dictionary contains data about 82 Gdańsk physicians from the second quarter of the sixteenth century to the early eighteenth century, arranged in chronological order, and was not completed due to the death of the author. This is a valuable contribution to the history of medicine in Gdańsk, in particular after it was supplemented by Schlieff, who benefitted from a more copious range of sources than the one at the disposal of his predecessor.